How triathletes mount their bikes after first transition (T1). A proposal of classification - Romero-Ramos, Óscar; Fernández-Rodríguez, Emilio; Merino-Marban, Rafael (My University, 2016)
A proposal is submit for the classification referring to the different ways in which triathletes mount their bikes to start pedalling. This action happens at the end of the transition area (T1) after having gone across on foot, with the bikes at their side, or, led across by hand, in a specific way (Fernández, Romero, Merino and April, 2015). These are unique aspects of this sport, compared to other sports in which a bike is also used. The purpose of this research was concentrates in describing and classifying the motor behaviours that occur at the end of the transition area, in front of the “judge’s line”. This study was bassed on participants of 3 Spanish Elite Championships of different distances (407 triathletes). It was filmed in the moment when they picked up their bikes, passed through the transition area and mounted their bikes. Eleven different ways were discovered on how to mount a bike when passing the judge’s line.
Keywords: Triatlón; Triathlon; Mount-dismount line; Judge’s line; T1